Conducting High acetic acid and temperature acetification processes by Acetobacter pasteurianus UMCC 2951. (November 2020) - Pothimon, Ruttipron; Gullo, Maria; La China, Salvatore; Thompson, Anthony Keith; Krusong, Warawut
Graphical abstract: Highlights: High initial acetic acid-high temperature acetification (HTA) process is explored. Long adaptation cultivation cycles provide stable acetic acid productions. CaCl2 can improve strength of acetic acid bacteria (AAB) cells and activities. Prototype scale of HTA is tested for solving the major lack in controlled process. Implementing the HTA respect to the optimal AAB growth, reducing production costs. Abstract: In this study Acetobacter pasteurianus strain UMCC 2951 was tested as a microbial starter to conduct acetification processes by repeatedly cultivation cycles under high temperature acetification at 40 ± 1 °C. Acid production and acetification rate increased with repeated cultures under high temperature acetification as adaptation period increased, but were still lower than acetification at 30 ± 1 °C. However, the addition of 0.15 % calcium chloride reduced the negative effects of 40 ± 1 °C on both acid production and acetification rate compared to 30 ± 1 °C. A strong decrease in fatty acids and phosphatidylethanolamine and increases in phosphatidylcholine and phosphatidylglycerol in cell membranes were found under high acid and high temperature acetification. In addition, transmission electron microscope images reveal a more compact cell wall when calcium chloride was added to the cultivation medium. The strategy used in this study confirmed that the use of acetic acid bacteria as microbial starters could be effective also at temperature above the optimal values, when acetification processes are managed through repeated semi-continuous cycles.